Preoperative serum circulating microRNAs as potential biomarkers for chronic postoperative pain after total knee replacement. (October 2020) - Giordano, Rocco; Petersen, Kristian Kjær; Andersen, Hjalte Holm; Lichota, Jacek; Valeriani, Massimiliano; Simonsen, Ole; Arendt-Nielsen, Lars
Background: Chronic postoperative pain affects approximately 20% of patients with knee osteoarthritis after total knee replacement. Circulating microRNAs can be found in serum and might act as biomarkers in a variety of diseases. The current study aimed to investigate the preoperative expression of circulating microRNAs as potential predictive biomarkers for the development of chronic postoperative pain in the year following total knee replacement. Methods: Serum samples, collected preoperatively from 136 knee osteoarthritis patients, were analyzed for 21 circulatory microRNAs. Pain intensity was assessed using a visual analog scale before and one year after total knee replacement. Patients were divided into a low-pain relief group (pain relief percentage <30%) and a high-pain relief group (pain relief percentage >30%) based on their pain relief one year after total knee replacement, and differences in microRNAs expression were analyzed between the two groups. Results: We found that three microRNAs were preoperatively dysregulated in serum in the low-pain relief group compared with the high-pain relief group. MicroRNAs hsa-miR-146a-5p, -145-5p, and -130 b-3p exhibited fold changes of 1.50, 1.55, and 1.61, respectively, between the groups (all P values < 0.05). Hsa-miR-146a-5p and preoperative pain intensity correlated positively with postoperative pain relief (respectively, R = 0.300, P = 0.006; R = 0.500, P < 0.001). Discussion: This study showed that patients with a low postoperative pain relief present a dysregulation of circulating microRNAs. Altered circulatory microRNAs expression correlated with postoperative pain relief, indicating that microRNAs can serve as predictive biomarkers of pain outcome after surgery and hence may foster new strategies for preventing chronic postoperative pain after total knee replacement (TKR).